Learning Progression–Based Assessments: A Systematic Review of Student and Teacher Uses. (December 2022) - Harris, Lois Ruth; Adie, Lenore; Wyatt-Smith, Claire
This systematic review examined evidence of the utility of learning progression (LP)–based assessments to inform teaching and student learning in classroom contexts. Fifty-nine studies met inclusion criteria and were analyzed against four research questions. Evidence highlighted their potential for supporting judgments about learning, informing instructional and learning decisions, and improving teacher learning and development. Although 23 studies measured student achievement, reporting positive overall effects, only 6 adopted the experimental designs necessary for causal claims. Using LP-based assessment for formative purposes was well supported. Limited evidence was found regarding summative and accountability uses. Findings show that LP-based assessment design and use requires trade-offs relating to standardization and scale. Teachers need opportunities for negotiation when making judgments and integrating LP-based assessments into existing curriculum and policy contexts. Future research should examine student use of LP assessments and find a balance between standardization and customization to meet the needs of diverse learners and local contexts.